The effects of sample preparation on the interlaminar shear strength test values of unidirectional carbon fiber-reinforced epoxy composites. Issue 4 (May 2019) - Sun, Ying; Lu, Yonggen; Guo, Xiaoye
Interlaminar shear strength (ILSS) is an important indicator to measure the interfacial adhesion between the fiber and the matrix. The ILSS values of the unidirectional carbon fiber-reinforced epoxy composites prepared under different process conditions were investigated. Three main factors in the sample preparation, namely pressure in the molding process, fiber content of the composite, and whether to add vacuum treatment in the sample preparation process, were probed in this work. We found that the samples prepared under high pressure presented low ILSS values, but the sample prepared without pressure was not suitable for testing and the optimum pressure was 0.5 MPa. The sample prepared at lower fiber content was also not suitable for testing. However, the ILSS value decreased when the fiber content was further increased and the optimum fiber content was 60 wt%. The ILSS value was significantly increased by adding the process of vacuum treatment in the preparation.